Study of the Incorporation of Biomass Bottom Ashes in Ceramic Materials for the Manufacture of Bricks and Evaluation of Their Leachates - Terrones Saeta, Juan María; Suárez Macías, Jorge; Iglesias, Francisco Javier; Corpas Iglesias, Francisco Antonio (MDPI, 2020)
Scarcity of raw materials, reduction of greenhouse gas emissions and reduction of waste disposal in landfills are leading to the development of more sustainable building materials. Based on these lines, this work studies the incorporation of biomass bottom ashes into ceramic materials for brick manufacture, in order to reuse this currently unused waste and reduce clay extraction operations. To this end, different groups of samples were made with different combinations of clay and biomass bottom ashes, from 100% clay to 100% biomass bottom ashes. These samples were shaped, sintered and subjected to the usual physical tests in ceramics. In turn, the mechanical resistance, color and leaching of the contaminating elements present were studied. The physical and mechanical tests showed that the results of all the families were adequate, achieving compressive strengths of over 20 MPa and leaching of the contaminating elements acceptable by the regulations. Therefore, a sustainable range of ceramics was developed, with specific properties (porosity, density, resistance and color), with a waste that is currently unused and sustainable with the environment.
Keywords: ceramic; brick; biomass bottom ash; clay; compression resistance; leachate; environment; circular economy; sustainability